An Organizational Field Approach to Corporate Rationality: The Role of Stakeholder Activism - O’Connell, Lenahan L. (Business ethics quarterly, 2005)
This paper contends that rationality is more properly evaluated as a property of an organization’s relationships with its stakeholders than of the organization itself. We predicate our approach on the observation that stakeholders can hold goals quite distinct from those of owners and top managers, and these too can be rationally pursued. We build upon stakeholder theory and Weber’s classic distinction between wertrationalitat and zweckrationalitat, adding to them the “new institutionalist” concept of the organization field (1983, 1991). Stakeholders employ a variety of direct and indirect mechanisms to rationalize relations with the firm. We discuss four: internal subunits, legislated stakeholder participation, legislated access to information, and direct stakeholder activism. These developments are blurring the distinction between the environment and the organization by importing the values and goals of external stakeholders into the internal organization. They are also precipitating a more structured set of relationships among the actors who comprise the field. To the extent that the zweckrationalitat values of managers and owners as well as the wertrationalitat concerns of stakeholders are met, the firm is more rational.